Amphiphilic block copolymer poly(lactic acid)‐block‐(glycidylazide polymer)‐block‐polystyrene: synthesis and self‐assembly. Issue 7 (21st April 2017) - Li, Guoping; Dong, Haoxue; Liu, Menghui; Xia, Min; Chai, Chunpeng; Luo, Yunjun
Abstract: The triblock energetic copolymer poly(lactic acid)‐ block ‐(glycidylazide polymer)‐ block ‐polystyrene (PLA‐ b ‐GAP‐ b ‐PS) was synthesized successfully through atom‐transfer radical polymerization (ATRP) of styrene and ring‐opening polymerization ofd, l ‐lactide. The energetic macroinitiator GAP‐Br, which was made from reacting equimolar GAP with α ‐bromoisobutyryl bromide, firstly triggered the ATRP of styrene with its bromide group, and then the hydroxyl group on the GAP end of the resulting diblock copolymer participated in the polymerization of lactide in the presence of stannous octoate. The triblock copolymer PLA‐ b ‐GAP‐ b ‐PS had a narrow distribution of molecular weight. In the copolymer, the PS block was solvophilic in toluene and improved the stability of the structure, the PLA block was solvophobic in toluene and served as the sacrificial component for the preparation of porous materials, and GAP was the basic and energetic material. The three blocks of the copolymer were fundamentally thermodynamically immiscible, which led to the self‐assembly of the block copolymer in solution. Further studies showed that the concentration and solubility of the copolymer and the polarity of the solvent affected the morphology and size of the micelles generated from the self‐assembly of PLA‐ b ‐GAP‐ b ‐PS. The micelles generated in organic solvents at 10 mg mL −1 copolymer concentration were spherical but became irregular when water was used as a co‐solvent. The spherical micelles self‐assembled in toluene had three distinct layers, with the diameter of the micelles increasing from 60 to 250 nm as the concentration of the copolymer increased from 5 to 15 mg L −1 . © 2017 Society of Chemical Industry Abstract : Spherical micelles with three distinct layers were obtained from the self‐assembly of PLA‐ b ‐GAP‐ b ‐PS triblock copolymers in toluene, which was the basis for forming porous energetic skeleton of nano‐energetic materials.